마늘잎마름병균(Stemphylium vesicarium)에 대한 효율적인 마늘의 저항성 검정법 개발 - 이진주(Jin Ju Lee); 김헌(Hun Kim); 김진철(Jin-Cheol Kim); 최경자(Gyung Ja Choi) (Weon'ye gwahag gi'sulji, 2022)
Stemphylium vesicarium에 의해서 발생하는 잎마름병은 마늘의 Allium 속의 작물에서 발생하는 곰팡이병으로, 마늘의 품 질을 저하시키고 생산량을 감소하는 등 큰 피해를 주고 있다. 본 연구는 잎마름병에 대한 마늘의 저항성을 효과적으로 검정하 기 위한 방법을 확립하기 위해, 마늘의 품종, 마늘의 생육 시기, 접종원의 농도, 접종원에 포함된 영양분 종류, 접종 후 배양 온도 에 따른 마늘의 잎마름병 발생을 조사하였다. 실험한 결과로부터, 마늘의 잎마름병 저항성을 검정하기 위해서는 마늘 인편을 원예용 상토에 파종한 후, 온실(25 ± 5°C)에서 재배하여 준비한 4엽기 식물체에 접종 직전에 탈색한 비흡수성 재질의 솜으로 문지른 후에 멸균한 50% PDB로 수확한 S. vesicarium의 포자현탁액(3.0 × 105 spores/mL)을 분무하여 접종한다. 그리고 접 종한 식물체를 20°C의 습실상에서 48시간 동안 습실 처리하고, 마늘 유묘를 25°C의 항온항습실(상대습도 80%)로 이동하여 하루에 12시간씩 광을 조사하면서 재배하고, 품종에 따라 접종 7–11일 후에 잎에 발생한 잎마름병의 병반면적율(%)을 조사 하는 것을 제안하고자 한다. 본 연구에서 확립한 마늘 잎마름병 저항성 검정 방법은 잎마름병에 대한 저항성 육종 소재의 발굴 및 저항성 품종 개발에 활용될 수 있을 것이다. Leaf blight caused by Stemphylium vesicarium is an important fungal disease of the Allium genus, which decreases the quality and seed yield of garlic (Allium sativum). To establish an efficient screening method for testing the resistance of garlic cultivars to S. vesicarium, we measured leaf blight development on garlic plants according to cultivar, plant growth stage, inoculum concentration, nutrient source contained in the spore suspension, and incubation temperature. We determined that the most efficient method to develop leaf blight on garlic plants involved the following procedures: First, garlic cloves were grown in horticultural soil and cultivated in a greenhouse (25 ± 5°C). Seedlings at the four-leaf stage were rubbed with bleached, nonabsorbent cotton and spray-inoculated with a spore suspension (3.0 × 105 spores/mL) of the fungus composed of sterilized 1/2 potato dextrose broth. The inoculated plants were incubated in a dew chamber at 20°C for 48 hours, and then the infected seedlings were cultured in a growth chamber at 25°C and 80% RH under 12-hour light per day. Seven days after inoculation, infected leaf area (%) was measured. Our screening system can be used to select resistant resources and develop S. vesicarium-resistant garlic cultivars. KCI Citation Count: 4